2021
DOI: 10.3389/fpsyg.2021.646334
|View full text |Cite
|
Sign up to set email alerts
|

Suffering and Salutogenesis: A Conceptual Analysis of Lessons for Psychiatry From Existential Positive Psychology (PP2.0) in the Setting of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has had a widespread effect on the thoughts, emotions and behavior of millions of people all around the world. In this context, a large body of scientific literature examining the mental health impact of this global crisis has emerged. The majority of these studies have framed this impact in terms of pre-defined categories derived from psychiatric nosology, such as anxiety disorders, depression or post-traumatic stress disorder. These constructs often fail to capture the complexity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 106 publications
(125 reference statements)
1
5
0
1
Order By: Relevance
“…In line with previous studies ( 28 , 30 , 33 ), we have identified GRR in relevant vulnerable groups as a critical premise in designing mental health intervention programs. The concept of SOC can influence some psychotherapeutic modalities and psychological counseling approaches.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In line with previous studies ( 28 , 30 , 33 ), we have identified GRR in relevant vulnerable groups as a critical premise in designing mental health intervention programs. The concept of SOC can influence some psychotherapeutic modalities and psychological counseling approaches.…”
Section: Discussionsupporting
confidence: 83%
“…We expected a substantial association and prognosis of SOC both in line with burnout and in line with personal accomplishment as an aspect to mental health. The need for proactive research to identify GRR in this group is outlined ( 28 , 30 , 32 , 33 ).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Sense of coherence is described as one’s ability to holistically comprehend a stressful experience, the capacity to use the available resources, and the enduring and dynamic feeling of confidence that the experiences in life are comprehensible, manageable, and meaningful [ 17 ]. The concept called ‘salutogenesis’ focuses on our innate capacity to create and maintain health and well-being in the face of adversity [ 18 ], and more on people’s resources than on pathogenesis [ 19 ]. Our internal healing resources and potential for active adaptation to new circumstances is emphasised in the salutogenic model [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facing some adversity as opposed to none or extreme levels of adversity actually appears to improve coping ability, functioning, and happiness (Seery et al, 2010). Positive Psychology 2.0 (Wong, 2011), Existential Positive Psychology (Wong, 2020; Wong et al, 2021) and salutogenesis (Antonovsky, 1979; Rajkumar, 2021) may all contribute to boosting resiliency, positive wellbeing, and possibly even flourishing during these times of ongoing adversity. In fact, proactive coping with “suffering can enhance our resilience” (Wong et al, 2021, para.…”
Section: Responding To Heterogeneous Situations and Building Resiliencementioning
confidence: 99%